2020
DOI: 10.1111/hae.13962
|View full text |Cite
|
Sign up to set email alerts
|

Do patients with von Willebrand disease exhibit higher blood loss and revision rates in hip and knee arthroplasty? A case‐control study

Abstract: Background:The aim of the study was to compare the perioperative blood loss, need for transfusion and one-year revision rates in patients undergoing hip and knee arthroplasty who also have a diagnosis of von Willebrand disease (VWD) with a matched control group. Methods:A retrospective single-centre case-control study was conducted. Fiftyeight patients with VWD and 116 controls (1:2 match) who were operated for primary or revision hip and knee arthroplasty at our hospital were included. Blood loss, haemoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…12 13 using Hb in patients with von Willebrand disease using different methods. 12 Good et al reported that as a method of evaluating blood loss during TKA, calculating blood loss through a suction bottle and drain was routine. However, since the method did not evaluate hidden blood loss due to hematoma in the joint or thigh after tourniquet release, blood loss was calculated using the Hb balance method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12 13 using Hb in patients with von Willebrand disease using different methods. 12 Good et al reported that as a method of evaluating blood loss during TKA, calculating blood loss through a suction bottle and drain was routine. However, since the method did not evaluate hidden blood loss due to hematoma in the joint or thigh after tourniquet release, blood loss was calculated using the Hb balance method.…”
Section: Discussionmentioning
confidence: 99%
“…Blood loss increases when TKA is performed in patients with haemophilia compared to that in patients without bleeding disorders such as idiopathic osteoarthritis. 12 13 using Hb in patients with von Willebrand disease using different methods. 12 Good et al reported that as a method of evaluating blood loss during TKA, calculating blood loss through a suction bottle and drain was routine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations